2019
DOI: 10.3390/vetsci6020036
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Liver Transcriptome among Cattle Breeds Using RNA-seq

Abstract: Global gene expression in liver transcriptome varies among cattle breeds. The present investigation was aimed to identify the differentially expressed genes (DEGs), metabolic gene networks and metabolic pathways in bovine liver transcriptome of young bulls. In this study, we comparatively analyzed the bovine liver transcriptome of dairy (Polish Holstein Friesian (HF); n = 6), beef (Hereford; n = 6), and dual purpose (Polish-Red; n = 6) cattle breeds. This study identified 895, 338, and 571 significant (p < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 71 publications
1
5
0
1
Order By: Relevance
“…Though the library prep kit used is apt at maximizing sequencing depth when compared with other commercial solutions, we noticed that many transcripts with (typically) a relatively low expression were either not detected or detected at very low level, with zero-counts in most samples. Despite being able to detect >14,000 transcripts with a count>4 in at the least one sample, which is somewhat similar to what previously reported in RNAseq analysis of bovine liver ( 125 127 ), many transcripts with a relatively medium-low expression were either not detected or detected at very low level, with lack of detection in most samples. Most of the genes used for the RT-qPCR were in this category, such as all PPAR transcripts and LIPC .…”
Section: Limitationssupporting
confidence: 87%
“…Though the library prep kit used is apt at maximizing sequencing depth when compared with other commercial solutions, we noticed that many transcripts with (typically) a relatively low expression were either not detected or detected at very low level, with zero-counts in most samples. Despite being able to detect >14,000 transcripts with a count>4 in at the least one sample, which is somewhat similar to what previously reported in RNAseq analysis of bovine liver ( 125 127 ), many transcripts with a relatively medium-low expression were either not detected or detected at very low level, with lack of detection in most samples. Most of the genes used for the RT-qPCR were in this category, such as all PPAR transcripts and LIPC .…”
Section: Limitationssupporting
confidence: 87%
“…Filters for differentially expressed genes between preadipocytes and mature adipocytes can promote further study of fat deposition in goats. Numerous studies have shown that RNA-seq helps reveal transcriptome differences in tissues and cells [29][30][31][32]. In this study, the DEG-Seq was used to analyse the DEGs in intramuscular preadipocytes and adipocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in the context of library complexity plot, duplicate reads are those that map to the same location with same orientation. However, in the post-alignment QC analysis (Figure 4), StrandNGS tool was successfully performed the alignment or mapping of the processed pre-alignment RNA-seq data on the Bos Taurus reference genome to identify the number of aligned reads, uniquely aligned reads, which was very critical and crucial for the genetic variants or single nucleotide polymorphisms (SNPs) discoveries [21,22] and identification of DEGs, gene network and metabolic pathways in bovine liver and pituitary tissues [23,24].…”
Section: Discussionmentioning
confidence: 99%